Indeks Kepuasan Masyarakat terhadap Kualitas Pelayanan Program Demang Dimmas (Kademangan Digital Melayani Masyarakat) di Kecamatan Kademangan Kota Probolinggo - Verto Septiandika; Nur Halima (Sawala : Jurnal Administrasi Negara, 2021)
In line with the times and technology, especially the changes that occur in society that affect the needs of the community, public services provided by both government and private agencies continue to provide good, effective, and easy innovations. One of them is at the kelurahan level, which is the government agency closest to the community. One of them is Ketapang Village, Kademangan District, Probolinggo City, which has an online technology-based service innovation. This study aims to determine the level of community satisfaction with the quality of service innovation of the Demang Dimmas Program (Kademangan Digital Melayani Masyarakat) in Ketapang Village, Kademangan District, Probolinggo City. In this study the method used is descriptive quantitative, in accordance with the formulation of the problem that is descriptive. Quantitative research is descriptive and tends to use an inductive approach to analysis. The sampling technique used in this study is a non-probability sampling technique with the type of accidental sampling, namely the technique of determining the sample based on the spontaneity factor. The research sample is targeted at 100 respondents according to the minimum number of respondents in the preparation of the Community Satisfaction Index which was chosen accidentally. Based on the calculation of the Community Satisfaction Index, the service quality of the Demang Dimmas Program (Kademangan Digital Melayani Masyarakat) in Ketapang Village, Kademangan District, Probolinggo City obtained an IKM conversion result of 69.19. The performance of the service unit of the Demang Dimmas Program (Kademangan Digital Melayani Masyarakat) in Ketapang Village, Kademangan District, Probolinggo City is in the "C" service quality with the "Poor Good" category.